Analysis of Tambau Water Pollution Levels Through Histopathology of Nilem Fish (Osteochilus vittatus) - Atifah, Yusni; Arianti, Riri Putri; Vauzia, Vauzia; Satria, Rijal (Jurnal Perikanan Universitas Gadjah Mada, 2024)
Tambau Lake is a lake used by the community to cultivate fish. The quality of lake waters can be reflected through animals that live in lake waters such as fish. Fish that have been polluted with pollutant compounds for a long period of time will experience structural and functional abnormalities, as well as changes in histological conditions. This study aims to determine the level of water pollution in Tambau Lake through histopathological studies of Osteochilus Vittatus gills. This type of research is a descriptive analysis using a survey method of Tambau Lake and Osteochilus vittatus. Determination of Osteochilus vittatus and water samples using purposive random sampling method. Preparation using paraffin method and hematoxylin-eosin staining. The results of the study were then analyzed descriptively based on the level of damage to the gill tissue structure with the level of water pollution. The results of histopathological analysis on Osteochilus vittatus gill samples found damage to the presence of (a) edema (cell swelling), (b) hyperplasia which causes other damage, namely (clubbing tissue shaped like a baseball bat and thickening of cartilage) and (c) secondary lamella fusion which continues to become (telangiectasis) which indicates that Tambau Lake water is experiencing moderate - severe pollution. This is also in line with simple water quality results (physical, chemical and biological tests) which showed that the level of pollution was classified as severe.